A Influência da Inflexão Costeira na Variabilidade da Linha de Praia em Mostardas – RS - ABSALONSEN, LUCIANO; TOLDO JR, ELÍRIO (Pesquisas em Geociências, 2007)
<!-- .justificar { text-align: justify; } --> Mostardas beach, with an approximate extension of 36 km, is located along the intermediate section of Rio Grande do Sul state's coastline; its north and south limits are São Simão beach and Mostardas lighthouse, respectively. At the northern portion of the beach, an anomalous depositional behavior is found, relative to most beaches along the state coast. The anomalous behavior observed at this beach strip is influenced by a nearly 11º change in beach orientation. Such inflexion makes the wave energy act differently in beach strips located north and south from the inflexion, as examined in both seasonal and annual scales. Within a given seasonal scale, the morphology will be shaped according to events that the beach was subjected to, leaving the beach surface even, low, and regular with the passage of storm events, and acquiring a greater sediment stock at its subaerial portion in low-sea conditions, thus marking this beach seasonality. Yearly variability, verified at an 8-year interval between monitoring conducted in 1997 and 2005, demonstrated that the southern half of this beach shows erosion in almost its totality. The pattern in the 17 km of the northern half is quite different, with a significant enhance of stability and depositional areas, 36.1 and 28.1 %, respectively, and a seaward progradation mean of 1.1 m/year. The northern half also shows progradation areas between 3 and 4 times longer than those found in previous researches made on the Rio Grande do Sul coast (Toldo et al., 1999; Esteves et al., 2002). Such behavior confirms that the coastal inflexion found at the place significantly contributes with the shoreline variability in Mostardas beach.